PERSIAPAN PEREMAJAAN KEBUN KELAPA SAWIT OLEH KUD SUKA MAJU DAN KUD BUKIT JAYA DI KABUPATEN DHARMASRAYA PROPINSI SUMATERA BARAT - Melinda Noer; Ira Wahyuni Syarfi; Rafnel Azhari (Buletin Ilmiah Nagari Membangun, 2019)
Nationally, the program to rejuvenate oil palm has become a concern of the Government. It is supported by the policy of replanting grant funds using funds from the Oil Palm Plantation Fund Management Agency (BPDPKS), including West Sumatra Province. In Dharmasraya District, KUD Suka Maju received grant funds to realize replanting in 2019, while KUD Bukit Jaya was for realization in 2020. This paper describes the activities' results to the two KUDs in preparation for replanting oil palm using BPDPKS funds. The activity's objective is to encourage and revive the spirit of cooperation in the KUD and help accelerate the effective coordination among stakeholders in the replanting program in the district of Dharmasraya. In the context of broader regional development, particularly the development of sustainable oil palm plantations, this oil palm replanting program needs to involve stakeholders from the initial planning stages to implementation and evaluation. Coordination between related government agencies requires the participation of the Regional Development Planning Agency (Bappeda) as the coordinator of regional planning, and it is necessary to internalize the replanting program plan with all its aspects into the Office's Strategic Plan (Renstra) and the Regional Medium-Term Development Plan.